MORPHOLOGICAL, PHYSIOLOGICAL AND BIOCHEMICAL ADAPTATION OF WHEAT (Triticum aestivum L)TO DROUGHT STRESS - MUHAMMAD, A.; ABUBAKAR, I.A.; SALE, S; ABDULMUMINI F (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Agriculture and crop productivity have been seriously threatened by water scarcity. Given how damaging the stress is and how long it lasts, losses from drought are likely greater than losses from all other causes. Wheat has experienced the consequences of drought stress on its morphological, physiological, and biochemical characteristics as well as effects on growth, water relations, and photosynthesis. Wheat responds to prevailing water stress in a range of morphological, physiological, and biochemical ways at the cellular and molecular levels, making it a complicated phenomenon. Stress from drought has an impact on root growth, stem lengthening, and leaf size, as well as on the relationship between plants and water and the efficiency of water usage.Numerous physiological studies are being conducted to learn more about the alterations that drought stress causes in wheat plants. There are two techniques to examine morphological changes: changes in the root system and changes in the shoot system, such as effects on height, leaf senescence, flowering, and so on. Alterations in chlorophyll content, perturbations in photosynthetic processes, and plant-water relationships are examples of physiological alterations. In various chemicals, biomolecules, and enzymes, biochemical changes take place. This review summarizes the adaptation of wheat to drought stress on growth and productivity. This review could be useful for wheat researchers and growers for making the right decision on the breeding effort intending to create a drought tolerant variety under water limited regions and selection of wheat genotype that can endure water scarcity.